Perbandingan Portofolio Saham Dengan Metode Capital Asset Pricing Model Dan Arbitrage Pricing Theory (Studi Kasus Pada Perusahaan Transpotasi Sub Sektor Maskapai Penerbangan Yang Terdaftar Di Bursa Efek Indonesia 2019-2021) - Japlani, Ardiansyah; Ali, Karnila; Prabowo, Bob Ardi (Jurnal Manajemen DIVERSIFIKASI, 2023)
Regulations restricting transportation services have caused a drop in revenue and profits for transportation companies, and some companies have even suffered losses. This decrease in the number of passengers will have an impact on the financial performance of airline companies in Indonesia. The purpose of this research is to find out how to analyze stock portfolios, find out why investors need the CAPM and APT methods in maximizing stock portfolios and compare the accuracy of stock portfolio analysis in the airline sub-sector for the 2019-2021 period using the CAPM and APT methods. This research method uses descriptive quantitative research. The object of this research is stock performance. Data collection is carried out by means of a documentary study of close stock prices and macroeconomics. Data analysis used the CAPM and APT methods. The results of stock portfolio analysis using the CAMP and APT methods obtained securities that can produce maximum stock returns are PT Garuda Indonesia (GIAA). The CAPM and APT models can be used by investors to form a stock portfolio because it is easier and simpler. The CAPM model is more accurate than the APT model.